2010
DOI: 10.1038/nm.2175
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of histone H3 lysine 56 acetylation as an antifungal therapeutic strategy

Abstract: Candida albicans is a major fungal pathogen that causes serious systemic and mucosal infections in immunocompromised individuals. In yeast, histone H3 Lys56 acetylation (H3K56ac) is an abundant modification regulated by enzymes that have fungal-specific properties, making them appealing targets for antifungal therapy. Here we demonstrate that H3K56ac in C. albicans is regulated by the RTT109 and HST3 genes, which respectively encode the H3K56 acetyltransferase (Rtt109p) and deacetylase (Hst3p). We show that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
185
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(195 citation statements)
references
References 56 publications
9
185
0
1
Order By: Relevance
“…112 Amongst proteins within the HDAC complex, H3K56ac has a key role in the DNA damage response; this protein may be fungal-specific. 113 Effects on Candida. C. albicans have two distinct cell types-white and opaque-with phenotypic differences in cell shape, mating properties and virulence.…”
Section: Hdacismentioning
confidence: 99%
See 2 more Smart Citations
“…112 Amongst proteins within the HDAC complex, H3K56ac has a key role in the DNA damage response; this protein may be fungal-specific. 113 Effects on Candida. C. albicans have two distinct cell types-white and opaque-with phenotypic differences in cell shape, mating properties and virulence.…”
Section: Hdacismentioning
confidence: 99%
“…Finally, reduced levels of H3K56ac activity (regulated by the C. albicans RTT109 gene) have sensitized C. albicans to hydroxyurea, the azoles, and echinocandins and are associated with attenuated C. albicans virulence in mice. 113,120 Inhibition of Hst3p in C. albicans results in loss of cell viability with abnormal filamentous growth. 113 Researchers have tested the activity of at least one new HDACi, MG-CD290, against a range of Candida spp.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The Candida genome encodes for 3 sirtuins (HST1, HST2 and HST3). It has been shown that inhibition of HST3 by either gene repression or nicotinamide treatment reduces to a considerable extent the clinical severity of candidiasis 24 . In light of this reported observation, we checked for sirtuin like activity of purified Hos2 preparations using resveratrol, which activates sirtuins 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Gene inactivation experiments led to association of individual HDAC genes with morphological transitions, virulence and expression and regulation of important drug resistance associated proteins, as the chaperone Hsp90 protein and drug efflux pumps. [8][9][10][11] Interestingly, inactivation of C. albicans HDAC coding genes HDA1 and RPD3 led to reduced trailing growth and reduced capability to evolve azole resistance, possibly due to a effect of these HDACs on the expression regulation of efflux pumps. 12 In the pathogenic mold Aspergillus fumigatus, HDAC gene inactivation led to defects in germination and in secondary metabolite production.…”
mentioning
confidence: 99%